2012
DOI: 10.1121/1.3681937
|View full text |Cite
|
Sign up to set email alerts
|

Pitch strength of normal and dysphonic voices

Abstract: Two sounds with the same pitch may vary from each other based on saliency of their pitch sensation. This perceptual attribute is called "pitch strength." The study of voice pitch strength may be important in quantifying of normal and pathological qualities. The present study investigated how pitch strength varies across normal and dysphonic voices. A set of voices (vowel /a/) selected from the Kay Elemetrics Disordered Voice Database served as the stimuli. These stimuli demonstrated a wide range of voice quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
19
0
3
Order By: Relevance
“…In prior research, this measure has been shown to be a good predictor of listener perception of voice quality. 17,19 As stated previously, there are two significant advantages to using a bio-inspired approach to describe changes in voices. First, this does not rely on accurate estimation of F 0 , which makes this approach applicable to the vast majority of dysphonic voices, including those classified as Type 2 or 3 signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior research, this measure has been shown to be a good predictor of listener perception of voice quality. 17,19 As stated previously, there are two significant advantages to using a bio-inspired approach to describe changes in voices. First, this does not rely on accurate estimation of F 0 , which makes this approach applicable to the vast majority of dysphonic voices, including those classified as Type 2 or 3 signals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, voices perceived to be more breathy were found to have lower pitch strength when compared to voices judged as being less breathy. 17 Note that the term “pitch” is not used synonymously with “fundamental frequency.” While the two are correlated, the former is a perceptual phenomenon whereas the latter is a physical property of the signal. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, it has been shown that the relationship between a physical stimulus (dysphonic voice sample) and its perceptual attributes are often non-linear, yet can be successfully described by analytic models that include many of the nonlinear properties of the auditory system. 11–15 For example, modeling breathiness using auditory measures derived from a loudness model 16 resulted in better correlations with perceptual data than traditional acoustic measures such as cepstral peak prominence. 12, 17 In this model, the loudness elicited by the aperiodic components in the voice was computed as “noise loudness” or NL and the loudness elicited by the harmonic energy of the vowel that is masked by the aperiodic components of the same voice was computed as “partial loudness” or PL.…”
mentioning
confidence: 99%
“…15 Here pitch strength refers to how strong or faint a listener perceives the sensation of pitch in a sound stimulus. This quality is also referred to as “pitch salience.” For example, a sustained vowel like /a/ evokes a strong pitch sensation and thereby has higher pitch strength when compared to a fricative consonant like /s/.…”
mentioning
confidence: 99%
See 1 more Smart Citation